PENDIDIKAN KARAKTER PRESPEKTIF PENDIDIKAN ISLAM DALAM UPAYA DERADIKALISASI PAHAM RADIKAL - Irwan Fathurrochman; Eka Apriani (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2017)
The basis of character education in Islamic education is derived from the word akhlaq in plural form of khuluq which according to language is interpreted character, behavior, behavior or character. Essentially, character in education is the spirit in the Islamic education. Islamic education and character in education create students with better characters and values. It is clear that Islamic education with detailed guidance will never leave the content of Al-Quran and Al-Sunnah that in line with the character in education, in example building the students with good moral. There are seven characters that should be had by students namely emphaty, conscience, self control, respect, kidness, tolerance, and justice. The success of Islamic education does not depend on one component only but also all of education components.